1981
DOI: 10.1084/jem.153.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a human T lymphocyte surface protein associated with the E-rosette receptor.

Abstract: Human thymus-dependent lymphocytes (T cells) are defined by their ability to form spontaneous rosettes (E-rosettes) with sheep erythrocytes (SRBC) (1-3). Recently, several murine monoclonal antibodies that recognize distinct differentiation antigens on human T cells have been described (4-11). We report here a monoclonal antibody, designated 9.6, that identifies a 50,000-dalton surface protein that appears to be present on all E-rosette-forming cells. Blocking and lysostripping experiments indicate that this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
2

Year Published

1982
1982
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(70 citation statements)
references
References 20 publications
3
65
2
Order By: Relevance
“…In some experiments, PBMC were fractionated into E + and E-cell fractions by rosetting with 2-aminoethylisothiouronium bromide-treated sheep erythrocytes (33) and reconstituted at the indicated E+:E-cell ratios. T cells and NK cells both surface express CD2, which binds to sheep erythrocytes (34)(35)(36)(37), so the E + cell fractions predominantly contained T cells and NK cells.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…In some experiments, PBMC were fractionated into E + and E-cell fractions by rosetting with 2-aminoethylisothiouronium bromide-treated sheep erythrocytes (33) and reconstituted at the indicated E+:E-cell ratios. T cells and NK cells both surface express CD2, which binds to sheep erythrocytes (34)(35)(36)(37), so the E + cell fractions predominantly contained T cells and NK cells.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…It was first described as the sheep erythrocyte receptor because it induces T and NK cells to form rosettes upon incubation with sheep red cells (5). Engagement of the CD2 antigen with its ligands induces T-cell activation and proliferation (6).…”
mentioning
confidence: 99%
“…The current experiments demonstrated that the expression of the CD2 molecule, i.e., the E-rosette receptor (13,15,17,43), was elevated 10-to 20-fold on human T lymphocytes after activation. The elevation occurred on T cells that were activated either with PHA, which may directly interact with CD2, or with antibody to the CD3-Ti complex (Figs.…”
Section: Discussionmentioning
confidence: 58%
“…The E-rosette receptor (CD2) (13,15,17,43) is a differentiation antigen that occurs on virtually all T cells, whereas CD4 and CD8 identify T cell subsets (31). In addition to these differentiation antigens, there are also activation antigens that are expressed only on stimulated cells.…”
mentioning
confidence: 99%